Penggunaan metode L-moment dalam pemodelan hujan harian maksimum Kota Makassar - Wahidah Sanusi; Muhammad Abdy; Syafruddin Side (Seminar Nasional LP2M UNM, 2019)
Evaluation of maximum rainfall events is important in the management and planning of water sources which, among others, aim to design a drainage system and abundant water storage. This evaluation can be done through estimation of design rainfall. This rain design is very dependent on the type of distribution of opportunities for rain. Therefore, the purpose of this study was to identify the maximum distribution of rainfall opportunities in the city of Makassar using the L-Moment method. This method provides information about the size of the location, size of the spread, skewness and kurtosis of the distribution of probability data samples. The data used in this study is the annual maximum daily rainfall data of the Paotere Maritime Meteorology rain station in Makassar in the period 1985-2017. This station is selected based on the completeness and length of the data. Based on the good of fit distribution model, it was found that rainfall at the Paotere Maritime Meteorological Station followed the distribution of Generalized Logistics. The results of this study can then be used to estimate design rainfall